Pengenalan Dasar Akuntansi dan Legalitas Usaha EMKM guna Perluasan Segmen Pasar bagi Pelaku UMKM di Desa Pagedangan - Effriyanti, Effriyanti; Rahma Maulidia; Eko Sudarmanto; Citra Puspa Permata; Ibnu Aswat; Afridayani; Sri Rahayu; Yuliana (Ikatan Cendekiawan Muda Akuntansi, 2024)
Business legality is very important for a company to be able to operate safely and comfortably. Similarly, the recording and reporting of financial transactions is clean and in line with standards. However, not all MSMEs have business legality and transaction records that are neat and in accordance with accounting standards. Based on this background, lecturers from various universities and under the auspices of the professional organisation ICMA have collaborated to organise a community service in the form of an introduction to basic accounting and EMKM business legality for the expansion of the market segment for market segment for MSME actors in Pagedangan village. It is hoped that with the knowledge of business legality and with proper and standard accounting records, the MSMEs in Pagedangan Village will be able to expand their market share and progress in the future.